Multiobjective Hydraulic Design and Performance Analysis of a Vortex Pump Based on Orthogonal Tests - Hui Quan; Yongkang Wu; Ying Guo; Kai Song; Yanan Li (Shock and Vibration)
We design optimization on the overall blade structure of a vortex pump conducted by using the orthogonal test method to clarify the matching relationship of impeller and casing structures and then improve the hydraulic performance of the vortex pump. Based on two different impeller structures of forward-deflecting (denoted as R1 − F2) and backward-deflecting (denoted as F1 − R2), key parameters describing the impeller structure are calculated through optimization for the objective function of hydraulic efficiency by means of orthogonal tests and computational fluid dynamic simulations. Optimization computations show that the forward-deflecting blade impeller is superior to the backward-deflecting one. Model test of the optimized vortex pump is carried out calculating the error from the comparison of pump efficiencies calculated by model test and numerical simulation is calculated to be less than 6%. The experimental verification shows that the flow simulation has some errors. The weight of structure parameters such as the blade installation angle (α), the blade deflecting angle (β), the position of blade deflecting point (L), the radius (r) of smoothing arc at the deflecting point, the wedge type (W) of blade, to the lift head, the flow rate, and the efficiency of the pump is investigated, through multiparameter optimizations. Visualization observation of flows in the model pump consisted of a back-placed impeller and a front vaneless chamber is further performed. The characteristic of vortex formation predicted by flow simulation agrees with the result of visualization observation. The above results demonstrate that the optimum impeller type of vortex pump is forward-deflecting blade impeller. The optimum combination of the key structure parameters is that the deflection angle of the blade inlet (α) equals 30°, the position of blade deflecting point lM = 2/3 L, the chamfering radius (r) at the deflecting point r = 3 mm, and the best wedge type is axial deflecting blade.